Gambaran Pengetahuan Orang Tua dalam Penanganan Kejang Demam pada Anak Balita di Ruang Perawatan Anak Rumah Sakit Bhayangkara TK II Jayapura - Iriani Iriani; Nopi Nur Khasanah; Indra Tri Astuti (PPNI UNIMMAN, 2025)
Background: Febrile seizures are one of the most common emergencies in young children and can cause problems if not handled properly. Parents' understanding of how to handle febrile seizures greatly influences the initial steps taken when the incident occurs. This study aims to describe parents' knowledge in managing febrile seizures in children in the Pediatric Ward of Bhayangkara Hospital TK. II Jayapura. Method: This study is a descriptive study with one variable, namely parental knowledge about handling febrile seizures. The population consisted of all parents who have young children with a history of febrile seizures in the Pediatric Ward of Bhayangkara Hospital TK. II Jayapura, with a total of 36 respondents. Data collection was carried out using a validated and reliable questionnaire. Data analysis was carried out univariately and presented in the form of frequency distribution and percentage. Results: The results showed that of the 79 respondents, most parents had good knowledge about handling febrile seizures, some had moderate knowledge , and a small number had poor knowledge . Parents with good knowledge amounted to 38%, moderate knowledge 35.4%, and poor knowledge 26.6 %. Conclusion: Most parents in this study showed good knowledge in managing febrile seizures in young children. However, continuous education is still needed to improve the understanding of parents with moderate and poor levels of knowledge.